Sustainable application of GF-6 WFV satellite data in desert steppe: A village-scale grazing study in China - Zhang, Yuxun; Wang, Lei; Yang, Xinguo; Sun, Yuan; Song, Naiping (Frontiers in Environmental Science, 2023)
This study investigated the vegetation growth and forage-livestock balance of desert grasslands at the village scale. This study was chosen to be conducted in the Ningxia Hui Autonomous Region, where desert grasslands are widely distributed and fragility of the environment. This paper establishes a model for estimating time series changes of above-ground biomass (AGB) in the study area based on remote sensing images from the Gaofen-6 satellite, combined with canopy spectra and AGB data of vegetated desert steppe areas. Next, the ecological carrying capacity and load of the desert steppe area were analyzed based on the number of sheep raised in different enclosures and the grazing methods employed. The status of the forage-livestock balance in the study area was assessed after measuring the crop yield of farmland. Finally, data and case support for grazing management in desert steppe were provided in combination with the research results. The study concluded that Gaofen-6 satellite images could quickly and accurately obtain information on vegetation growth and changes in desert grassland areas at a village scale. The available grazing time in a single year in the study area is inadequate to support current stocking levels. When ecological stability is the primary consideration, natural forage obtained through natural conditions cannot meet the needs of farmers for normal grazing and production activities. The suitable grazing time in the study area is limited in any year. The suitable maximum grazing intensity among all plots ranged from 0.334 to 2.541 sheep/ha. In the case of the balance between grass and livestock, the forage obtained from natural pastures could only satisfy 41.71% of the current stocking levels for sheep. Rotational grazing and subsidies for farmers help desert steppe to recover and achieve a forage-livestock balance.